Review of interactions between high‐risk pediatric heart transplant recipients and marginal donors including utilization of risk score models. (20th March 2020) - Gossett, Jeffrey G.; Amdani, Shahnawaz; Khulbey, Sanjeev; Punnoose, Ann R.; Rosenthal, David N.; Smith, Jonathan; Smits, Jacqueline; Dipchand, Anne I.; Kirk, Richard; Miera, Oliver; Davies, Ryan R.
Abstract: Background: Donor organ acceptance practices vary among pediatric heart transplant professionals. We sought to understand what is known about the interactions between the "high‐risk" recipient and the "marginal donor, " and how donor risk scores can impact this discussion. Methods: A systematic review of published literature on pediatric HTx was undertaken with the assistance of a medical librarian. Two authors independently assessed search results, and papers were reviewed for inclusion. Results: We found that there are a large number of individual factors, and clusters of factors, that have been used to label individual recipients "high‐risk" and individual donors "marginal." The terms "high‐risk recipient" and "marginal donor" have been used broadly in the literature making it virtually impossible to make comparisons between publications. In general, the data support that patients who could be easily agreed to be "sicker recipients" are at more risk compared to those who are clearly "healthier, " albeit still "sick enough" to need transplantation. Given this variability in the literature, we were unable to define how being a "high‐risk" recipient interplays with accepting a "marginal donor." Existing risk scores are described, but none were felt to adequately predict outcomes from factors available at the time of offer acceptance. Conclusions: We could not determine what makes a donor "marginal, " a recipient "high‐risk, " or how these factors interplay within the specific recipient‐donor pair to determine outcomes. Until there are better risk scores predicting outcomes at the time of organ acceptance, programs should continue to evaluate each organ and recipient individually.